Effects of impeller speed and aeration rate on flotation Performance of sulphide ore - Yang, Z.; Aldrich, Chris (Elsevier, 2006)
The effects of aeration rate and impeller speed on the concentrate sulfur grade and recovery for batch flotation of a complex sulphide ore were investigated. The relationships between the water recovery and solid entrainment were discussed. It is found that the solid entrainment is linearly related to the water recovery regardless of aeration rate and impeller speed, and the higher sulfur recovery at the aeration rate of 2 and 4 L/min for the impeller speed of 1 500 r/min is considered to be the contribution of true flotation. Finally, the sulfur recovery flux is correlated with the bubble surface area flux based on the froth image at the different aeration rates and impeller speeds.